THE HEALTH PROMOTION MEDIA TO INCREASE COMMUNITY’S POSITIVE PERCEPTION ABOUT COVID-19 VACCINATION IN KENDARI CITY: HEALTH PROMOTION ABOUT COVID-19 - Tassya Enggartini Insani; Tasnim Tasnim; Erwin Azizi Jayadipraja (STIKes Mandala Waluya Kendari, 2022)
Background: The achievement of Covid-19 vaccination in Southeast Sulawesi Province until June 15, 2021 is 15.5%, while the City of Kendari has achieved Covid-19 vaccination reached 22%. The lack of information and public perception about the Covid-19 vaccine has led to low public acceptance of the Covid-19 vaccine. Therefore, this study aims to increase the community 's positive perception of the Covid-19 vaccination in Kendari City through the most effective health promotion media. Methods: This quantative study uses a quasi-experimental design with pretest-posttest nonequivalent control group design. The population is 345,107 people, 396 respondents are sampled. This study uses a sampling technique by random cluster sampling. The hypothesis test used is the Wilcoxon signed ranks test and the Kruskal Wallis H test. Result: The results of the Wilcoxon test show that there is a significant difference between perceptions before and after health promotion using booklet media (Asymp. Sig. = 0.000); There is a significant difference between perceptions before and after health promotion using video media (Asymp. Sig. = 0.000); There is a significant difference between perceptions before and after health promotion through the development WhatsApp messages (Asymp. Sig. = 0.000). Based on the Kruskal Wallis H test, the mean rank of health promotion using booklets is the highest (217.59). There was no significant difference between the three media (Asymp. sig 0.156 > 0.05). Conclusion: The booklet is the most effective media in health promotion to increase the positive perception of the community towards the covid-19 vaccination in the city of Kendari, but there is no significant difference between the three promotional media used.